Actors in the road transit of goods from Mali and Niger via Burkina Faso and regional integration of WAEMU - (:unkn) unknown (My University, 2022)
The international road transport of goods, which accounts for 90% of trade in West Africa, should be an essential sector for the strengthening of regional integration in the area of the West African Economic Monetary Union (WAEMU). This article therefore aims to analyze the roles of the main actors in the road transit of goods from Mali and Niger via Burkina Faso in relation to the process of regional integration. This research is essentially based on qualitative interviews with the main actors in the field and a quantitative survey carried out among road drivers in Mali and Niger involved in the transit of goods through Burkina Faso. Overall, the analysis shows that multi-sector integration institutions, the West and Central African Ports Management Association, chambers of commerce and shippers' councils are institutional actors that have missions to promote regional integration. Truck drivers, for their part, are real players in regional integration from below. However, the security or control forces are above all those which, through their actions in the transport sector, constitute obstacles to the strengthening of the regional integration process.
Keywords: African Research